Abnormalities in emotional and motor reactions among young prehypertensive individuals: employing continuous blood pressure analysis. Issue 10 (October 2021) - Wiener, Avigail; Goldstein, Pavel; Doenyas, Keren; Okon-Singer, Hadas
Abstract : Background: Essential hypertension is an important risk factor for cerebrovascular diseases and a major cause of premature death in industrialized societies. A predisposing factor for essential hypertension is prehypertension: blood pressure (BP) values at rest that are at the higher end of the normal range. Abnormally enhanced cardiovascular responses to motor and emotional tasks have been found as predictors of essential hypertension. Yet, knowledge regarding the BP reaction to aversive stimuli and motor reaction in prehypertension is limited. Methods: We compared the reaction to aversive and neutral stimuli inducing an emotional response (experiment 1) and to the isometric handgrip exercise (IHE) inducing a motor response (experiment 2), between prehypertensive and normotensive controls. BP reactions were measured and analyzed in a continuous fashion, in contrast to previous studies that averaged BP responses across blocks. We applied a multilevel B-spline model, a continuous analysis that enabled a better understanding of the BP time course and the detection of subtle differences between groups. Results: In both tasks, we found that prehypertensive individuals showed enhanced DBP reactions compared with normotensive controls; prehypertensive individuals exhibited lower BP responses to aversive pictures and higher BP responses to the IHE. These results are in line with previous studies with healthy or hypertensive participants and suggest abnormalities already in the prehypertensive stage. Conclusion: Considering the high frequency and health risks related to prehypertension, understanding the autonomic reactions to emotional and motor stimuli in this population is of clinical and theoretical importance and could serve as a behavioural marker to identify at-risk groups. Abstract : Supplemental Digital Content is available in the text